Photon emission as a characterization tool for bipolar parasitics in FinFET technology. (September 2018) - Beyreuther, A.; Herfurth, N.; Amini, E.; Nakamura, T.; De Wolf, I.; Boit, C.
Abstract: Parasitic bipolar effects are a well-known failure mechanism in integrated circuits. They trigger latching phenomena and are of particular interest for higher current applications and under leaky conditions. Photon emission microscopy (PEM) has proven to be a suitable tool to detect the occurrence of parasitic bipolar elements in MOSFETs, such as the parasitic bipolar junction transistor (BJT). Spectral PEM even allows for a more detailed characterization of the respective parasitic bipolar operation modes. In this work, we show that spectral PEM can also be used to characterize bipolar parasitics in modern p-type and n-type FinFETs. Additionally, this characterization method allows us to determine whether germanium enriched silicon was used to optimize device performance. We conclude by demonstrating that the FinFET devices under test show a very good suppression of parasitic bipolar effects.